2005
DOI: 10.1111/j.1467-9523.2005.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Farm and Off‐farm Work and Life Satisfaction Among Norwegian Farm Women

Abstract: Previous research has showed that farmers and spouses having off‐farm work report higher life satisfaction than those who work only on the farm. Using both quantitative and qualitative data we test this correlation and ask whether there are other factors than just the off‐farm work which might explain this. Data from a national survey, involving 935 farm women, and in‐depth interviews with twenty‐five farm women, are used to explore the relation between work situation and life satisfaction. The analysis shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
2
13
0
4
Order By: Relevance
“…This most probably leads to higher satisfaction, as their labour situation is the result of their own preferences. The same holds true for the women who deliberately choose to work on the farm (Haugen and Blekesaune 2005). The female respondents in this study working off the farm belong to the group that deliberately chooses to do so.…”
Section: Resultsmentioning
confidence: 87%
“…This most probably leads to higher satisfaction, as their labour situation is the result of their own preferences. The same holds true for the women who deliberately choose to work on the farm (Haugen and Blekesaune 2005). The female respondents in this study working off the farm belong to the group that deliberately chooses to do so.…”
Section: Resultsmentioning
confidence: 87%
“…Many women need to be at home in the morning or afternoon, of both, for caring or domestic responsibilities. Mothers especially tend to organise their paid work around these responsibilities, either in order to solve childcare problems or fulfil their commitments (Stone 1990; Braithwaite 1994; Halliday 1997; Little 1997; Bennett 2004; Bock 2004; Dobbs 2005; Haugen and Blekesaune 2005).…”
mentioning
confidence: 99%
“…It has recently been shown that combining on‐farm and off‐farm occupations decreases household income compared to specialized strategies (Mittenzwei and Mann forthcoming), another sign that diversification has disadvantages in terms of efficiency. For farmwomen, however, Haugen and Blekesaune () have shown that off‐farm occupations can increase life satisfaction.…”
Section: The Three Dimensions Of Workplace Diversification In Agriculmentioning
confidence: 99%